Compression Loss in Plywood-Experiments on Dalbergia sissoo - Shah, R. S. (Indian Forester, 1984)
Necessity of the precise data on compression loss in plywood is being felt by the industry, as it is one of the most important factors wbich can considerably add to the economy. In the present paper, data On the compression loss on Dalbergia sissoo is reported. It has been found that compression loss decreases with the increase in thickness of the plywood, for the same pressure.